Patria Mud Body Modification Study on Komatsu HD785-7 Unit for Overburden Transportation - Supriyanto Supriyanto; Joshua Pribadi Wikan; Steven Tammu; Aadjudia Prida Pratama; Muhammad Rafly Adha; Anggun Azis Mulyanti (Jurnal Indonesia Sosial Teknologi, 2024)
Coal mining activities require reliable means of transportation to support productivity and safety. PT AMM site ABP Energy uses a Komatsu HD785-7 off-highway dump truck with a Mud Body vessel and a Std Light Vessel which has significant differences in empty weight and payload capacity. The heavier Vessel Mud Body increases fuel consumption and the risk of overloading. This study aims to examine the modification of the Mud Body vessel to be lighter without reducing the payload capacity. The methods used include secondary data collection from technical specifications and modification simulation analysis. The results of the study show that the partial cutting of the side wall vessel of the Mud Body can reduce the empty weight by up to 3,345 kg, close to the specifications of the standard vessel. These modifications improve fuel efficiency, minimize the risk of overloading, and maintain the reliability of the unit. In conclusion, planned modifications are effective in improving operational efficiency and lowering operational costs without sacrificing safety and productivity.